Cover Feature: (C4C1Im)6[Hg7Se10]: The Salt of a Molecular Selenido Mercurate Anion Obtained from Ionic Liquids (Z. Anorg. Allg. Chem. 22/2018). Issue 22 (27th November 2018) - Donsbach, Carsten; Dehnen, Stefanie
Abstract : The cover picture shows different views of the unprecedented molecular structure of the binary selenido mercurate anion [Hg7 Se10 ] 6–, which was obtained in a top‐down synthesis from the ternary selenido mercurate K2 [Hg2 Se3 ] exhibiting a 3D structure. Treatment of the latter in the ionic liquid (C4 C1 Im)[BF4 ] (C4 C1 Im = 1‐butyl‐3‐methylimidazolium) and small amounts of 1, 2‐diaminoethane (en) at 80°C afforded the title compound (C4 C1 Im)6 [Hg7 Se10 ] as light‐yellow single‐crystals. The structure was determined by X‐ray diffraction, and the Hg:Se ratio was confirmed by micro X‐ray fluorescence spectroscopy. More details can be found in the article by Carsten Donsbach, and Stefanie Dehnen on page1383 ff .